Impact of Low PM2.5 Exposure on Asthma Admission: Age-Specific Differences and Evidence from a Low-Pollution Environment in China - Xiaolong Fan; Chen Yang; Jinsheng Chen; Yuping Chen; Gaojie Chen; Ziyi Lin; Zecong Li; Yanting Chen; Liqian Yin; Lingling Xu; Naian Xiao (Aerosol and Air Quality Research)
Abstract Many epidemiological studies focus on health research in areas with high concentration of PM2.5. To fill the research gap, our study investigated the acute effects of low PM2.5 level (annual average concentration below 35 µg m−3) on asthma admissions in Xiamen, China. Using a time-stratified case-crossover study design, we examined the association between PM2.5 concentration and asthma admissions from January 2019 to November 2021. The results showed a positive correlation between PM2.5 concentration and the cumulative incidence of asthma, with a lag of 0–7 days. Each 10 µg m−3 increased in PM2.5 concentration was associated with a 0.49% increase in asthma incidence. Stratified analysis revealed significant effects in children aged 0–4 years (OR = 2.029, 95% CI = 1.359–3.031) and the elderly population aged over 75 years (OR = 1.399, 95% CI = 1.092–1.793). Distributed lag models demonstrated a hysteresis effect, with significant lagged effects observed in children (lag0–5) and the elderly (lag3–lag5). The multi-pollutant model, considering NO2 and O3, showed consistent results. These findings highlight the age-specific susceptibility to PM2.5 exposure and its impact on asthma admissions, even at lower levels of pollution. Further research is needed to inform environmental protection policies and public health interventions in low-pollution environments.